PENGARUH LATIHAN DUMBBLE CURL TERHADAP KEKUATAN OTOT LENGAN DAN BAHU ATLET PUTRI FPTI PEKANBARU - Riantama, Rifaldi; ', Slamet; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This study was conducted to determine whether there is influence of dumbble curl exercises on the muscle strength of the arms and shoulders on athletes FPTI daughter Pekanbaru in order to get maximum results at the time of climbing. Problems encountered during observation are not reaching a good time of 10 seconds on average, falling during jab, not reaching top. This is thought to be weak muscle strength of arms and shoulders. The purpose of this study was to see the effect of dumbble curl exercise on muscle strength of arms and shoulders at FPTI daughter of Pekanbaru. The form of this study is experimental (experimental) research, with population of female athletes FPTI Pekanbaru, the sample in this study is the entire population of 6 people. Instruments performed to determine the strength of the muscles of the arms and shoulders, in this study is the test of expanding dynamometer. After that, the data were processed with statistics, to test the normality by lilifors test at a significant level of 0.05?. The hypothesis proposed is the influence of dumbble curl exercise on the muscle strength of the arm and shoulders of the FPTI daughter of Pekanbaru. Based on t test analysis yield Thitung of 2.402 and Ttable 2.015, means Thitung> T table. Based on statistical data analysis, there is an average pree-test of 11.83 and a mean post-test of 14, then the data is normal. Thus Ha is accepted, there is a dumbble curl exercise effect on the muscle strength of the arms and shoulders at the FPTI female athlete Pekanbaru.Key Words: Dumbble Curl, Arm and Shoulder Strength